Interaction of Beta-Hydroxy-Beta-Methylbutyrate Free Acid and Adenosine Triphosphate on Muscle Mass, Strength, and Power in Resistance Trained Individuals. Issue 7 (July 2016) - Lowery, Ryan P.; Joy, Jordan M.; Rathmacher, John A.; Baier, Shawn M.; Fuller, John C.; Shelley, Mack C.; Jäger, Ralf; Purpura, Martin; Wilson, Stephanie M.C.; Wilson, Jacob M.
Abstract : Abstract: Lowery, RP, Joy, JM, Rathmacher, JA, Baier, SM, Fuller, JC Jr, Shelley, MC II, Jäger, R, Purpura, M, Wilson, SMC, and Wilson, JM. Interaction of beta-hydroxy-beta-methylbutyrate free acid and adenosine triphosphate on muscle mass, strength, and power in resistance trained individuals. J Strength Cond Res 30(7): 1843–1854, 2016—Adenosine-5′-triphosphate (ATP) supplementation helps maintain performance under high fatiguing contractions and with greater fatigue recovery demands also increase. Current evidence suggests that the free acid form of β-hydroxy-β-methylbutyrate (HMB-FA) acts by speeding regenerative capacity of skeletal muscle after high-intensity or prolonged exercise. Therefore, we investigated the effects of 12 weeks of HMB-FA (3 g) and ATP (400 mg) administration on lean body mass (LBM), strength, and power in trained individuals. A 3-phase double-blind, placebo-, and diet-controlled study was conducted. Phases consisted of an 8-week periodized resistance training program (phase 1), followed by a 2-week overreaching cycle (phase 2), and a 2-week taper (phase 3). Lean body mass was increased by a combination of HMB-FA/ATP by 12.7% ( p < 0.001). In a similar fashion, strength gains after training were increased in HMB-FA/ATP-supplemented subjects by 23.5% ( p < 0.001). Vertical jump and Wingate power were increased in the HMB-FA/ATP-supplemented group compared with the placebo-supplemented group, and the 12-week increases were 21.5 and 23.7%, respectively. During the overreaching cycle, strength and power declined in the placebo group (4.3–5.7%), whereas supplementation with HMB-FA/ATP resulted in continued strength gains (1.3%). In conclusion, HMB-FA and ATP in combination with resistance exercise training enhanced LBM, power, and strength. In addition, HMB-FA plus ATP blunted the typical response to overreaching, resulting in a further increase in strength during that period. It seems that the combination of HMB-FA/ATP could benefit those who continuously train at high levels such as elite athletes or military personnel.